Investment plans, innovations and revision costs in Finnish manufacturing - Ilmo Pyyhtiä (Bank of Finland, 1991)
In this paper the reasons for revisions of announced investment plans are analyzed theoretically and empirically. In earlier studies by the author it was shown that investment plans and final investments differ systematically from each other. The theoretical framework is based on neoclassical investment theory, rational expectations and partial adjustment of investment plans. The effects of uncertainty are also studied. The empirical results show that investment plans are endogeneous to the firm and can change as the picture of demand or relative prices of factors of production change. So, the information set relevant to the determination of investment plans can be defined with conventional investment theory. According to the estimation results, reactions to shocks decrease when the survey horizon shortens. This supports the hypothesis on the increasing revision costs of investment plans as the realization time approaches. The results concerning demand uncertainty give some support to the theoretical result that an increase in demand uncertainty may reduce investments.
URN:NBN:fi:bof-201908081367
Keywords: 330